Red zones: criminal law and the territorial governance of marginalized people - Sylvestre, Marie-Eve; Blomley, Nicholas K.; Bellot, Céline (Cambridge University Press, 2019)
"In [this book the authors] examine the court-imposed territorial restrictions and other bail and sentencing conditions that are increasingly issued in the context of criminal proceedings. Drawing on extensive fieldwork with legal actors in the criminal justice system, as well as those who have been subjected to court surveillance, the authors demonstrate the devastating impact these restrictions have on the marginalized populations (the homeless, drug users, sex workers and protesters) who depend on public spaces. On a broader level, the authors show how red zones, unlike better publicized forms of spatial regulation such as legislation or policing strategies, create a form of legal territorialization that threatens to invert traditional expectations of justice and reshape our understanding of criminal law and punishment"–Publisher's website
OCLC: 1097459847